Fungsi Sastra Lisan Cerita Rakyat Dusun Ngareng Desa Jatimulyo - Mas Rurotul Umah (Signifiѐ, 2024)
By studying the literary works contained in an area, various cultural views can be obtained that are preserved in a society. Because literature is an integral part of culture. This study aims to discuss the function of oral literature in Ngareng Hamlet, Jatimulyo Village. Oral literature that is still being preserved is folklore. Behind this oral story there are several functions. The function of oral literature is the function of oral literature as entertainment, the function of oral literature as cultural validation, the function of oral literature as a regulator of community norms and behavior, and the function of oral literature as disaster mitigation.